The determinants of dividend declared by the selected GLICs in Malaysia / Claudia Arjoe Octiviananda Jihan Abdul Rahman - Abdul Rahman, Claudia Arjoe Octiviananda Jihan (2018)
GLICs is stand for Government Linked Investment Companies that control the primary objective of Government Linked Companies (GLCs). GLICs has control over a GLCs when it is the majority shareholder or single largest shareholder and when it has the ability to exercise and influence major decisions such as appointment of board members and senior management. There are 7 companies that referred as the GLICs in Malaysia and they are Minister of Finance Incorporated (MOF Inc), Permodalan Nasional Berhad (PNB), Khazanah Nasional Berhad (KNB), Employment Provident Fund (EPF/KWSP), Lembaga Tabung Angkatan Tentera (LTAT), Tabung Haji (LTH) and Kumpulan Wang Persaraan (KWAP). In this study, the regression model used is ordinary least square (OLS) in order to test the relationship between the dependent variable and independent variables. The regression will be regress by using panel data. The period of study is 10 years which are from 2007 until 2016. The fluctuation of dividend declared might be from internal and external factors of the company. The internal factors such as the firm size, leverage and profitability of the company while for the external factors such as Gross Domestic Product (GDP), interest rate and inflation rate. This study holds a purpose to identify the determinants that influence the dividend declared by the selected GLICs in Malaysia which are TH, EPF, and LTAT. From the previous study that related, the researchers found there are positive relationship between the profitability and dividend and also between firm size and dividend but negative relationship between leverage and dividend. For the macroeconomic variables which is the external factors, past researchers expect it to be positive relationship with the dividend. Therefore, this study will investigate the determinants that influence the dividend declared by selected GLICs.